Comparison of Perception of God and Life Expectancy among Veterans with Spinal Cord Injuries, Chemical Veterans, and Ordinary People; A Case Study of Urmia City - L. Hasani Tabatabai; A. Shaker dioulagh (Afarand Scholarly Publishing Institute, 2018)
Aims: Studies have shown that the perception of God and life expectancy are important in adapting to chronic diseases and their consequences. The purpose of this study was to compare the level of perception of God and life expectancy among the veterans with spinal cord injuries, chemical veterans, and ordinary people. Instruments & Methods: The present study was a causal-comparative study conducted in Urmia in 2016. 30 veterans with spinal cord injuries were selected by census method, 50 chemical veterans were randomly selected and 50 ordinary people were selected by cluster sampling. The research instruments were perception of God Scale and Millerchr('39')s Hope Questionnaire (MHS). Data were analyzed by multivariate analysis of covariance analysis, multivariate analysis of variance analysis and Bonferroni post hoc test, using SPSS 22 software. Results: In the total score of perception of God, there was a significant difference between chemical veterans and ordinary people (p=0.001). In the challenge component, there was a significant difference between chemical veterans and ordinary people (p=0.003) and between veterans with spinal cord injuries and ordinary people (p=0/011). Also there was a significant difference in life expectancy between two groups of chemical veterans and veterans with spinal cord injuries (p=0.007). Conclusion: There is a difference between the level of perception of God and the life expectancy among the veterans with spinal cord injuries, chemical veterans, and ordinary people.